Is it all death feigning? Case in anurans - Toledo, Luís Felipe; Sazima, Ivan; Haddad, Célio F.B. [UNESP] (Taylor & Francis, 2010)
Anurans are known to feign death as a way to avoid or minimize the risk of predation. However, information on this defensive strategy is scattered and we believe that there is more than one behaviour type referred to as thanatosis. Here we review the literature, add original data, and propose definitions and new names that complement the present knowledge on the subject. We collected information on 334 individuals of 99 species in 16 families and grouped the recorded displays into two categories of tonic immobility: (1) thanatosis, death-feigning, or playing possum, and (2) shrinking or contracting. These two categories are treated as different behaviour types because of the display pattern (position of fore- and hindlimbs, eye opening), presence of skin toxins (shrinking is mostly displayed by toxic species, whereas thanatosis is mostly displayed by non-toxic species), social context (interaction with predators), and their putative or actual functions. © 2010 Taylor & Francis.
Keywords: Anurans; Death feigning; Defensive behaviour; Shrinking; Thanatosis; Tonic immobility; behavioral ecology; defense behavior; frog; literature review; predation risk; species diversity; toxin; Anura